Implementation of the Problem-Based Learning Model with an Islamic Values Approach to Improve Students' Honest and Responsible Attitudes at MI Hidayatul Mubtadiin Sukorame - lutfi, Wahib (Jurnal Cendekia Islam Indonesia, 2025)
This study aims to implement the Problem-Based Learning (PBL) model with an Islamic values ​​approach to improve honesty and responsibility attitudes of grade 3 students of MI Hidayatul Mubtadiin Sukorame Gandusari Trenggalek East Java. Honesty and responsibility are important characters that need to be developed early on, especially in an educational environment based on Islamic values. The research method used is classroom action research (CAR) with two cycles, involving planning, implementation, observation, and reflection. Data collection was carried out through observation, interviews, and questionnaires which were analyzed descriptively qualitatively and quantitatively. The results of the study showed that the application of the PBL model with an Islamic values ​​approach significantly improved students' honesty and responsibility attitudes. This can be seen from the increase in honesty and responsibility scores measured through behavioral observations and student questionnaires in each cycle. In addition, students are more active in the learning process, more open in expressing opinions, and more responsible in completing assignments. Thus, the PBL model based on Islamic values ​​is effective in instilling positive attitudes in students and can be an alternative learning strategy applied in Islamic elementary schools or Islamic-based elementary schools